Protective Effects of Ginger Extract on NAFLD-Associated Male Infertility in Rats: Hormonal Regulation and Semen Quality - Abdalla Elgenaidi,; Alnagy Ali,; Hanan Miftah,; Fatema Alsaeid, (AlQalam Journal of Medical and Applied Sciences, 2026)
Non-alcoholic fatty liver disease (NAFLD) is a highly prevalent metabolic disorder that extends beyond hepatic pathology to adversely affect male reproductive function through hormonal dysregulation and systemic metabolic disturbances. Zingiber officinale (ginger), a medicinal plant rich in bioactive compounds, has been reported to exert beneficial effects on metabolic and reproductive health. The present study investigated the protective role of aqueous ginger extract against NAFLD-induced reproductive dysfunction in male rats. NAFLD was experimentally induced in adult male Wistar rats by feeding a high-fat diet (HFD). Animals were allocated into control, HFD control, and treatment groups receiving either 10% or 20% aqueous ginger extract. Sperm parameters, including concentration, motility, and morphology, were evaluated alongside serum testosterone and luteinizing hormone (LH) levels. Hepatic function was assessed by measuring serum alanine aminotransferase (ALT) and aspartate aminotransferase (AST). Data were analyzed using one-way ANOVA followed by Tukey’s post hoc test.